2020
DOI: 10.1111/apha.13541
|View full text |Cite
|
Sign up to set email alerts
|

The role of RIPK3‐regulated cell death pathways and necroptosis in the pathogenesis of cardiac ischaemia‐reperfusion injury

Abstract: Despite advancements in management of acute myocardial infarction, this disease remains one of the leading causes of death. Timely reestablishment of epicardial coronary blood flow is the cornerstone of therapy; however, substantial amount of damage can occur as a consequence of cardiac ischaemia/reperfusion (I/R) injury. It has been previously proposed that the pathway leading to major cell death, apoptosis, is responsible for cardiac I/R injury. Nevertheless, there is compelling evidence to suggest that necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 74 publications
(318 reference statements)
3
35
0
1
Order By: Relevance
“…Contrary to apoptosis, necrosis is a death program that does not depend on caspase. Necrosis mainly depends on RIPK1, RIPK3, and MLKL signaling (Ying, Benjanuwattra, Chattipakorn, & Chattipakorn, 2020). Our data revealed that AFB1 exposure promoted necrosis activation of HEMECs, which was distinctly ameliorated by Se treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to apoptosis, necrosis is a death program that does not depend on caspase. Necrosis mainly depends on RIPK1, RIPK3, and MLKL signaling (Ying, Benjanuwattra, Chattipakorn, & Chattipakorn, 2020). Our data revealed that AFB1 exposure promoted necrosis activation of HEMECs, which was distinctly ameliorated by Se treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of functional cardiomyocytes and increased fibrosis are responsible for cardiac contractile dysfunction and failure [ 24 27 ]. Of note, necroptosis is inherently immunogenic since it leads to the disruption of plasma membrane, thereby causing the release of pro-inflammatory biomolecules (collectively called damage-associated molecular patterns, DAMPs) [ 13 , 57 , 58 ]. In addition, ongoing progression of chronic MI has been associated with diverse types of cell death mechanisms [ 13 ].…”
Section: Main Textmentioning
confidence: 99%
“…Both electrical and mechanical defects evolve in the inflamed myocardium as a consequence of progressive cardiomyocyte loss and abnormal extracellular matrix deposition [ 66 , 67 ]. Necroptosis is known as one of the regulated forms of necrosis that initiate a robust inflammatory response by a release of DAMPs from the disruption of the plasma membrane [ 58 ]. The consequence following RIPK3-mediated necroptosis is the aggravation of inflammatory processes in various organs, including the heart, intestine and skin [ 58 , 68 70 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations